A Mini-Review on In situ Biogas Upgrading Technologies via Enhanced Hydrogenotrophic Methanogenesis to Improve the Quality of Biogas From Anaerobic Digesters - Zhang, Le; Kuroki, Agnès; Tong, Yen Wah (Frontiers in Energy Research, 2020)
In the context of accelerating development of renewable and sustainable energy, biogas upgrading has attracted significant attention in order to yield high quality biomethane which can be utilized as an alternative to natural gas. Biogas upgrading techniques have been revolutionized in the past decade with the emergence of new strategies such as enhanced hydrogenotrophic methanogenesis. This review comprehensively summarizes the latest in situ biogas upgrading technologies via enhanced hydrogenotrophic methanogenesis in order to facilitate their development and commercial application: (1) hydrogen injection into anaerobic digesters for in situ enhancement of hydrogenotrophic methanogenic pathways, (2) membrane electrolysis-assisted CO2 extraction and bioelectrochemical removal of CO2, and (3) additives (e.g. ash, zero-valent iron and biochar). The key findings and technical limitations are summarized and critically analyzed for each in situ biogas upgrading technique. Additionally, potential industrial applications of these in situ biogas upgrading strategies in anaerobic digesters are also discussed, before concluding with their future development.